Awareness of dengue fever among school children: a comparison between private and government schools - Kalra, Shivani; Kaur, Jasbir; Sharma, Suresh Kumar (Indian Journal of Community Health, 2014)
Background: Dengue is the mosquito born viral disease spreading its tentacles all over the world. Dengue constitutes for major cause of deaths in children. According to WHO, globally it was estimated that approximately 70-100 million people were infected every year. Therefore, the study has been conducted with the aim to assess knowledge regarding dengue fever among school children. Methodology: Total of 500 children were selected from 9th and 10th class of private and government schools using total enumerative sampling technique. Data was collected using questionnaire method. After assessing knowledge classes were taken by investigators focusing on prevention of dengue fever. Results: Finding of study revealed that among Private schools excellent knowledge was found in 06 (01.2%) children, good in 123 (24.6%) children, average 112 (22.4%) children and poor in 02 (00.41) whereas in Government schools none of students had excellent knowledge, 76(15.2%) children were having good knowledge, 178(35.6%) children were having average knowledge & 03 (00.6) children were having poor knowledge. The mean knowledge scores were higher in students of Private schools i.e. 31.45 ± 6.41 as compared to students of Government schools i.e. 28.17 ± 5.39 at t=6.19 (p=0.00). Conclusion: It is concluded that majority of school students of private and government schools were having average knowledge regarding prevention of dengue fever. Therefore, there is need for further information, education and communication programs regarding prevention of dengue fever and this can be achieved by organizing health education campaigns in community involving schools.